Genomic analysis of Paenibacillus macerans strain I6, which can effectively saccharify oil palm empty fruit bunches under nutrient-free conditions - Uke, Ayaka; Sornyotha, Somphit; Baramee, Sirilak; Tachaapaikoon, Chakrit; Pason, Patthra; Waeonukul, Rattiya; Ratanakhanokchai, Khanok; Kosugi, Akihiko (My University, 2023)
The improper disposal of palm oil industrial waste has led to serious environmental pollution. In this study, we isolated Paenibacillus macerans strain I6, which can degrade oil palm empty fruit bunches generated by the palm oil industry in nutrient-free water, from bovine manure biocompost and sequenced its genome on PacBio RSII and Illumina NovaSeq 6000 platforms. We obtained 7.11 Mbp of genomic sequences with 52.9% GC content from strain I6. Strain I6 was phylogenetically closely related to P. macerans strains DSM24746 and DSM24 and was positioned close to the head of the branch containing strains I6, DSM24746, and DSM24 in the phylogenetic tree. We used the RAST (rapid annotation using subsystem technology) server to annotate the strain I6 genome and discovered genes related to biological saccharification; 496 genes were related to carbohydrate metabolism and 306 genes were related to amino acids and derivatives. Among them were carbohydrate-active enzymes (CAZymes), including 212 glycoside hydrolases. Up to 23.6% of the oil palm empty fruit bunches was degraded by strain I6 under anaerobic and nutrient-free conditions. Evaluation of the enzymatic activity of extracellular fractions of strain I6 showed that amylase and xylanase activity was highest when xylan was the carbon source. The high enzyme activity and the diversity in the associated genes may contribute to the efficient degradation of oil palm empty fruit bunches by strain I6. Our results indicate the potential utility of P. macerans strain I6 for lignocellulosic biomass degradation.
Keywords: Glycoside hydrolase; Nutrient-free; Oil palm empty fruit bunch; Paenibacillus macerans; Whole-genome sequencing